Analysis of Technical Performance, Recovery and Prevention of Injuries in Wrestling athletes - Juhanis, Juhanis; Aliriad, Hilmy; Da’i, Mohamad; Adi S; Taufik, Muhamad Syamsul; Saifuddin, Hasan (Cuestiones de Fisioterapia, 2025)
Injuries in wrestling are often caused by a variety of factors, including poor technique, muscle fatigue due to lack of adequate recovery, and the lack of a structured injury prevention programme. This study aims to analyse the relationship between technique performance and the risk of injury in wrestling athletes, by identifying how the quality of the techniques used can affect the potential injury experienced by athletes. The research method used is a quasi-experimental design with experimental procedures that include testing techniques, recovery and structured injury prevention. The experimental design was carried out in two main phases. The sample of the study amounted to 20 students who are members of the State University of Makassar wrestling athletes. Data analysis was conducted using SPSS version 23, including descriptive linear regression analysis, ANOVA test and correlation test to evaluate the relationship between technique efficiency, recovery and injury risk. The results showed a Pearson correlation between technique performance and recovery: strong positive correlation (r = 0.633; p = 0.003). Technique performance and injury prevention: very strong correlation (r = 0.789; p = 0.000). Recovery and injury prevention: strong positive correlation (r = 0.658; p = 0.002). These results emphasise that technical performance, recovery and injury prevention are closely interrelated and have a significant positive relationship. A good integration of strategies between these three aspects is important to improve the athlete's performance while reducing the risk of injury. Conclusion Technical performance, recovery and injury prevention show that success in wrestling depends not only on physical strength and competitive ability, but also on maintaining good technique and regular body care.